Cognitive Science and Health Bioinformatics Advances and Applications - Korrapati, Raghu B.; Divakar, Ch.; Devi, G. Lavanya; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book highlights the interdisciplinary study of cognition, mind and behavior from an information processing perspective, and describes related applications to health informatics. The respective chapters address health problem-solving and education, decision support systems, user-centered interfaces, and the design and use of controlled medical terminologies. Reflecting cutting-edge research on computational methods - including theory, algorithms, numerical simulation, error and uncertainty analysis, and their applications - the book offers a valuable resource for doctoral students and researchers in the fields of Computer Science and Engineering.
1.Designing Of Algorithm For Image Analysis In Genotyping Microarray Data Analysis -- 2.Sentimental Analysis on Cognitive Data using R -- 3.A Study On Proteins Associated With MODY Using Computational Biology -- 4.Automatic Region Segmentation and Variance based Multimodal Medical Image Fusion -- 5.Modelling And Docking Studies Of Alpha Glucosidase Involved In Diabetes -- 6.A Study On Anti-Cancer Activity Of Spinacia Oleracea Zinc Nano Particles -- 7.Computational prediction of ligands with multiple protein targets involved in Type II Diabetes -- 8.Predicting NTPase activity for protein belonging to E.coli -- 9.Insilico Binding Studies Of Reveratrol For Protective Effects In Neuro degeneration Using Glutamate Receptor 3b As Target Model -- 10.Rough Set Theory based Missing Value Imputation -- 11.Computational prediction and validation studies on a diverse dataset of COX-2 inhibitors COX-2 inhibitors using linear regression analysis -- 12.Insilico docking studies of Pyrimidol derivatives on CARP2protein: Modeling and Dynamics studies -- 13.Computational study of BDNF natural variants -- 14.Application of centrality measures in the identification of critical genes in Autism disorder.
Keywords: Computational intelligence; Medical informatics; Bioinformatics; Biomedical engineering; Computational Intelligence; Health Informatics; Computational and Systems Biology; Bioinformatics; Biomedical Engineering and Bioengineering